(untitled) (Research, Society and Development, 2023)
Chronic Lymphocytic Leukemia (CLL) is a proliferative B-cell neoplasm, promoting enlargement of the spleen, liver and lymph nodes, affecting mainly white males, with a high incidence after 65 years of age. Thus, we aimed to identify the prevalence of patients with CLL in the Extreme South of Bahia, analyzing the markers of laboratory diagnostic protocols. The present study is a retrospective cohort from 2015 to 2019, under CAAE Approval: 5.336.684 from CEP/CONEP, of medical records of patients with LLC performed at the High Complexity Oncology Unit - UNACON, located in the municipality of Teixeira de Freitas, Bahia. Thus, the results allowed us to find that, according to information from DATASUS, of the 82 diagnosed cases of chronic lymphoproliferative diseases, between 2015 and 2019 from the Extreme South of Bahia, six cases were of LLC. In the medical records there were clinical-epidemiological characteristics, 66.7% were in male patients; with 50% white and brown individuals, presenting lymphocytosis, thrombocytopenia and normocytic-normochromic anemia (50%), one case (16.7%) carrying Gumprecht’s Patches and one case (16.7%) presenting CD79 and IGV15. As for the conclusions, it was seen that the most used diagnostic markers comprised the performance of hematological tests such as hemogram and myelogram, including hematological/biochemical characteristics, especially lymphocytosis, leukocytosis, thrombocytopenia, anemia, with emphasis on immunophenotypic characteristics, by CDs 19 and 79, being the low prevalence in the Far South of Bahia of only 7.3% of cases diagnosed with LLC.